2017
DOI: 10.1111/jcpp.12774
|View full text |Cite
|
Sign up to set email alerts
|

Prereader to beginning reader: changes induced by reading acquisition in print and speech brain networks

Abstract: Background: Literacy acquisition is a demanding process that induces significant changes in the brain, especially in the spoken and written language networks. Nevertheless, large-scale paediatric fMRI studies are still limited. Methods: We analyzed fMRI data to show how individual differences in reading performance correlate with brain activation for speech and print in 111 children attending kindergarten or first grade and examined group differences between a matched subset of emergent-readers and prereaders.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

14
61
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 70 publications
(80 citation statements)
references
References 60 publications
(81 reference statements)
14
61
2
Order By: Relevance
“…The precuneus has been frequently invoked in studies of language comprehension (Binder et al, 2009;Price, 2012) and reading (Chyl et al, 2018;Rimrodt et al, 2009;Roe et al, 2018;Ryherd et al, 2018;Schulz et al, 2008Schulz et al, , 2009Shaywitz et al, 2002), and there is evidence to suggest it represents the extent to which attentional resources are allocated to these tasks (Kuperberg et al, 2003;Schulz et al, 2008Schulz et al, , 2009. Consistent with the current findings, several studies have demonstrated negative associations between activation in the precuneus and out-of-scanner reading (Chyl et al, 2018;Rimrodt et al, 2009;Ryherd et al, 2018).…”
Section: Decoding Correlatessupporting
confidence: 86%
“…The precuneus has been frequently invoked in studies of language comprehension (Binder et al, 2009;Price, 2012) and reading (Chyl et al, 2018;Rimrodt et al, 2009;Roe et al, 2018;Ryherd et al, 2018;Schulz et al, 2008Schulz et al, , 2009Shaywitz et al, 2002), and there is evidence to suggest it represents the extent to which attentional resources are allocated to these tasks (Kuperberg et al, 2003;Schulz et al, 2008Schulz et al, , 2009. Consistent with the current findings, several studies have demonstrated negative associations between activation in the precuneus and out-of-scanner reading (Chyl et al, 2018;Rimrodt et al, 2009;Ryherd et al, 2018).…”
Section: Decoding Correlatessupporting
confidence: 86%
“…The cross-modal integration of these auditory and visual processes results in a brain network of frontal, temporal, and parietal regions that is activated during both auditory word (speech) and visual word (print) processing, across languages and orthographies (Rueckl et al, 2015). This co-active network for auditory and visual language processes, also called print-speech convergence, is thought to emerge as a function of learning to read (Chyl et al, 2018). However, the cognitive abilities that precede and predict the emergence of this shared network, setting the stage for successful reading acquisition, remain unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Preston et al (2016) found that the extent of overlap in the activation associated with the processing of print and speech in L1 in seven-year olds was a strong predictor of the development of reading abilities two years later. These findings suggest that successful reading acquisition for L1 results in the reorganization of the oral language networks in the brain into amodal reading related systems (Chyl et al, 2018;S. J.…”
Section: Introductionmentioning
confidence: 84%